Clinicoepidemiological Pattern and Outcome of Poisoning in Children in a Tertiary Care Hospital of Western Nepal - Chaudhary, Nagendra; Gupta, Binod Kumar; Poudel, Astha; Chhetri, Pradip (Journal of Universal College of Medical Sciences, 2022)
INTRODUCTIONPoisoning in children is one of the leading public health problem in low and middle income countries and a common cause of morbidity and mortality.MATERIAL AND METHODSThis prospective observational study was conducted for one year from 1st June, 2019 to 31st May 2020 to study the clinicoepidemiological pattern and outcome of children with poisoning in a tertiary care hospital of western Nepal.RESULTSTotal 38 children with poisoning were admitted and enrolled during the study period. The frequency of poisoning in children aged 0-5 years, 6-10 years and 11-16 years were 47.4%, 18.4% and 34.2% respectively. Poisoning was predominant in females (n=21, 55.3%). Majority poisoning cases (55.3%) were noticed in between May to August. More than three-fourth of the poisoning cases were noticed in the afternoons and evenings. Pesticides (organophosphorus, fungicide, herbicide, aluminium phosphide, and household rodenticides/insecticides) constituted 55.7% of total poisoning cases. Household rodenticides/ insecticides, volatile hydrocarbons and organophosphorus poisonings were noticed in 23.7%, 15.8% and 13.2% respectively.Three-fourth of the cases were symptomatic during the presentation where vomiting (76.3%), abdominal pain (34.2%) and constricted pupils (18.4%) were three major clinical symptoms and signs due to poisoning. About 84.2% cases survived. Complications were observed in about 15.8% cases where shock and respiratory failure was seen in 10.5% each followed by pneumonia (7.9%) and hepatitis (5.3%).CONCLUSIONPoisoning was common in children less than 5 years of age and majority of them were accidental in nature. Household rodenticides/insecticides, volatile hydrocarbons and organophosphorus poisonings were common types of poisoning.